Camphor poisoning presenting as acute diffuse demyelination of brain - Manorenj, Sandhya; Inturi, Snehalatha; Pancheti, Narayana (International Journal Of Community Medicine And Public Health, 2016)
Camphor is a colorless substance available in solid and liquid form. Volatile oil form of camphor is the active ingredient of Vicks Vaporub, and Tiger Balm ointments. These ointments are commonly used as home remedies for treatment of cough, cold and for topical analgesics. They are inexpensive, over the counter remedies, hence widely used in India. Neurological complication due to camphor toxicity reported is headache, mental confusion and seizures. Here we report, a case of diffuse white matter lesions in a young female due to accidental camphor inhalation while working in factory that manufactures vicks and tiger balm. The case highlights camphor as a possible cause of toxic demyelination hence potentially exposed workers should be educated about health and safety measures to prevent such complication.